DISFEMIA DALAM KOLOM KOMENTAR AKUN INSTAGRAM LUCINTA LUNA - Imarotul Khoiriyah; Sri Yanuarsih; I Wayan Letreng (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The social media comment column is an indirect interaction between netizens and public figures who are active on social media. Everyone is free to express their opinion in the comments column they write, but there are some comments that contain elements of dysphemia. The aim of this research is to find out the language policies in Indonesian netizens' social media and to analyze the presence of elements of dysphemia in the comments written by these netizens. Dysphemia is an attempt to change a good meaning into a bad, rude and mocking meaning. This aims to bring down the victim and is an expression of someone's hatred, annoyance and dislike. Dysphemia is closely related to language politeness in terms of aspects of social media policy. There are 3 forms of dysphemia that will be analyzed in this article, namely, 1) Dysphemia in the form of physical insults, 2) Dysphemia in the form of gender insults, 3) Dysphemia in the form of praising to put down. Research data was taken over a certain period of time directly from the comments column of Lucinta Luna's Instagram account using quantitative descriptive methods with advanced note-taking techniques.